DAMPAK PILKADA SERENTAK 27 JUNI 2018 TERHADAP ABNORMAL RETURN DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM DI BEI - Zoraya, Intan; Murni, Trisna; Saputra, Fachri Eka; Bahri, Syamsul; Kananlua, Paulus Suluk (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose-Analyze and empirically test the difference in abnormal returns and trading volume activities before and after the simultaneous local elections on June 27, 2018. Design/methodology/approach-Data collection is done by the documentation method. Sampling was carried out using the purposive sampling method, with the sample criteria being that the company’s shares were listed as issuers on the IDX which were included in the LQ 45 group during the study period from June 25, 2018, to June 30, 2018, and actively traded during the study period.Findings- The results of this study indicate that the elections affect the Indonesia Stock Exchange. This can be seen from the difference in the average abnormal return and the average trading volume activity before and after the elections. Implications-The results of this study will be able to help provide relevant information for capital market players to be more sensitive to direct or indirect activities that can affect stock prices. Keywords: Abnormal Returns, Trading Volume Activities, Stock